PENGARUH CITRA PERUSAHAAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNAAN JASA PENGIRIMAN PAKET PT. POS INDONESIA (Studi pada Kantor Pos Johar Kota Semarang) - Yudha Widyantoro Prabowo; Apriatni Endang Prihatini; Bulan Prabawani (Universitas Diponegoro, 2015)
Corporate image will be the encouragement of someone before buying something. Especially in the field of services, service quality will be the consideration of a person before deciding. PT. Pos Indonesia pays attention to both these aspects in order to win the competition in the parcel business. The purpose of this research is to know the influence of the corporate image and service quality of usage decision of the parcel delivery service PT. Pos Indonesia. The method of this research is explanatory with data collection techniques through questionnaires and interviews .Accidental sampling techniques used with a sample of 100 people .Analysis of the technique used is quantitative by using a test of validity, reliability, the correlation coefficient, the coefficients determined, simple and multiple regression analysis, cross tabulation, and the significance test (t test and F test). The results showed that variable corporate image having the contribution of influence against variable usage decision at 21,8 percent. Variable service quality having the contribution of influence against variable usage decision at 21,5 percent. Variable corporate image and service quality having the contribution of influence jointly on variable usage decision at 23,1 percent. The suggestions that can be given in this research are the company expected improving their service standards with capable to serve customers well and prioritize customers needs, the speed of employees in providing service, and employee awareness to customers.